Adaptation and Validation of The Work-Family Balance Scale (Universitas Negeri Semarang, 2022)
The need for the availability of work-family balance measuring instruments in the Indonesian context is becoming an increasingly urgent thing, along with the increasing interest in research on the field of work and family. This study aims to test adapting and validating the Work-Family Balance Scale developed by Carlson, et al., (2009) into the Indonesian context. The trial was conducted on 104 women who worked as policewomen. A series of adaptation processes have been carried out, ranging from translation, equivalence testing, validation, and reliability testing. Validity of content was tested through the Content Validity Index (CVI) by involving several expert reviewers, and the validity of constructs, using Confirmatory Factor Analysis (CFA). Based on this trial process, it is known that the WFB construct meets all Goodness of Fit criteria (RMSEA ≤ 0.08; SRMR ≤ 0.05; NF ≥ 0.9; CFI ≥ 0.9). In addition, Construct Reliability (CR) values 0.87 and Average Variance Extracted (AVE) 0.53. Thus, the WFB Scale can be used as a valid and reliable measuring tool to measure work-family balance in the Indonesian context.Keywords: adaptation; validation; work-family balance; scale